DOP026 Efficacy and safety of dose escalation to tofacitinib 10 mg BID for patients with ulcerative colitis following loss of response on tofacitinib 5 mg BID maintenance therapy: results from OCTAVE open. (16th January 2018) - Sands, B E; Moss, A C; Armuzzi, A; Marshall, J K; Lindsay, J O; Sandborn, W J; Danese, S; Tsilkos, K; Lawendy, N; Zhang, H; Friedman, G S; Chan, G; et al.
Abstract: Background: Tofacitinib is an oral, small-molecule Janus kinase inhibitor that is being investigated for ulcerative colitis (UC). We evaluated efficacy and safety of tofacitinib dose escalation in patients with UC participating in an ongoing, open-label, long-term extension (LTE) study (OCTAVE Open, NCT01470612; data as of July 2016 [efficacy], December 2016 [safety]). Methods: OCTAVE 1 included induction (OCTAVE Induction 1 and 2), maintenance (OCTAVE Sustain) and LTE (OCTAVE Open) studies. OCTAVE Open included non-responders from OCTAVE Induction 1 and 2 and patients who completed or experienced treatment failure in OCTAVE Sustain. This analysis included the subpopulation of patients in OCTAVE Open who achieved clinical response following 8 weeks of induction therapy with tofacitinib 10 mg twice daily (BID), entered OCTAVE Sustain receiving tofacitinib 5 mg BID and experienced treatment failure between Week 8 and up to Week 52, and subsequently entered OCTAVE Open and were escalated to tofacitinib 10 mg BID. Treatment failure was defined as increase ≥3 points from maintenance study baseline total Mayo score, plus increase in rectal bleeding subscore and endoscopic subscore (ES) ≥1 point and absolute ES ≥2 after ≥8 weeks of maintenance therapy. We evaluated clinical response, mucosal healing and remission at Months 2 and 12 of OCTAVE Open using non-responder imputation, and evaluated safety throughout the study. Results: The dose escalation subpopulation comprised 58 patients in OCTAVE Open (out of 914 enrolled in the study). In patients escalated to tofacitinib 10 mg BID, clinical response, mucosal healing and remission rates were, respectively, 58.6%, 41.4% and 34.5% at Month 2, and 68.8%, 60.4% and 52.1% at Month 12 (Table). The safety profile of tofacitinib 10 mg BID in the dose escalation subpopulation was generally consistent with that observed in the overall study population (Table). 2 Conclusions: For patients who lost initial clinical response to tofacitinib 10 mg BID induction therapy while on tofacitinib 5 mg BID maintenance therapy, dose escalation back to 10 mg BID recaptured clinical response for most patients by Month 2, and was well-tolerated, with no new safety signals. Interpretation of adverse event rates is limited due to the small sample size. References: 1. Sandborn WJ, et al . Tofacitinib as induction and maintenance therapy for ulcerative colitis. N Engl J Med, 2017;376:1723–36. 2. Lichtenstein GR, et al . Tofacitinib, an oral Janus kinase inhibitor, in the treatment of ulcerative colitis: open-label, long-term extension study. Am J Gastroenterol, 2017;112(S1) [Abstract 714].